Scrotal abscess with a rare cause - Mansoor Khizer; Samujh Ram; AlAlayet Yasen (Wolters Kluwer Medknow Publications, 2009)
A 4-year-old boy presented with a short history of right-sided acute scrotal pain and swelling. At exploration, pus was found in the hemiscrotum but no local cause could be found. Further exploration showed the pus coming through a patent processus vaginalis from a collection in the right iliac fossa secondary to acute appendicitis.